PENEGAKAN HUKUM TERHADAP TINDAK PIDANA RINGAN DALAM MEWUJUDKAN RESTORATIVE JUSTICE - Syafruddin Syafruddin; Noval Forestriawan (Universitas Borneo Tarakan, 2022)
AbstractAs time goes by, the types and numbers of criminals are changing and increasing, impacting the facilities and infrastructure owned by law enforcement, namely overpopulation in several correctional institutions in Indonesia. Criminal law policies must also be adjusted based on the purpose of the punishment itself. Restorative Justice is one of the alternatives to achieving this goal, especially for perpetrators of minor crimes. The normative type is used in this research by prioritizing laws and regulations as the norm for assessment and leading to prescriptive. As for the results of this research, first: the existence of Restorative Justice in Indonesia has been running, mainly applied to some instances, such as Handling Children in Conflict with the Law, Narcotics Abusers and Minor Crimes. This emphasis is based on several regulations issued by each law enforcement agency. Second, the existence of Restorative Justice in the community is not fully understood well because several cases in this study indicate that there is still an understanding of the Restorative Justice model at the adjudication stage; these cases should be resolved at the investigation and prosecution stages. It is impressive that law enforcement officials still have not promoted Restorative Justice in some instances (minor crimes). As the best way to resolve cases at hand, as well as the community, this impacts the successful implementation of law enforcement oriented toward Restorative Justice. Keywords: Law Enforcement, Minor Crimes, Restorative Justice